2021
DOI: 10.30827/digibug.73873
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between service performance and physical strength focusing on speed and spin rate in Japanese elite junior tennis players

Abstract: The service is the most powerful and potential shot in tennis. To reach global elite status, Japanese players, being generally inferior in height, must overcome the limitations in service performance. If their height is insufficient, they must improve their service performance speed while maintaining the spin rate. Therefore, in this study, we aimed to examine the relationship between service performance according to the speed and spin rates and physical factors among national-level male and female junior tenn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…In this study, it was not possible to extract the physical strength factors affecting the spin rate of the service. According to previous study, no correlation was found between service spin and physical strength in male players, but a correlation was reported in female players ( Koya et al, 2021 ). However, due to the small number of participants, further research was needed ( Koya et al, 2021 ).…”
Section: Discussionmentioning
confidence: 80%
See 3 more Smart Citations
“…In this study, it was not possible to extract the physical strength factors affecting the spin rate of the service. According to previous study, no correlation was found between service spin and physical strength in male players, but a correlation was reported in female players ( Koya et al, 2021 ). However, due to the small number of participants, further research was needed ( Koya et al, 2021 ).…”
Section: Discussionmentioning
confidence: 80%
“…According to previous study, no correlation was found between service spin and physical strength in male players, but a correlation was reported in female players ( Koya et al, 2021 ). However, due to the small number of participants, further research was needed ( Koya et al, 2021 ). We examined more than 50 players this time, but the results were the same as that in the previous study.…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations